2022
DOI: 10.3389/fncir.2022.965172
|View full text |Cite
|
Sign up to set email alerts
|

Medial septum: relevance for social memory

Abstract: Animal species are named social when they develop the capability of complex behaviors based on interactions with conspecifics that include communication, aggression, mating and parental behavior, crucial for well-being and survival. The underpinning of such complex behaviors is social memory, namely the capacity to discriminate between familiar and novel individuals. The Medial Septum (MS), a region localized in the basal forebrain, is part of the brain network involved in social memory formation. MS receives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Therefore, the SuM could potentially provide two independent channels by which the cerebellum could influence both spatial (via SuM projections to the dorsal dentate gyrus) and social (via SuM projections to the CA2) hippocampal functions. However, as noted above, work by DuLac’s group suggests a lack of a disynaptic fastigial to hippocampus projection ( Fujita et al, 2020 ), and the SuM may instead route its influence on the hippocampus via e.g., the septum ( Pan and McNaughton, 2004 ; Griguoli and Pimpinella, 2022 ).…”
Section: The Social Hippobellum?mentioning
confidence: 99%
“…Therefore, the SuM could potentially provide two independent channels by which the cerebellum could influence both spatial (via SuM projections to the dorsal dentate gyrus) and social (via SuM projections to the CA2) hippocampal functions. However, as noted above, work by DuLac’s group suggests a lack of a disynaptic fastigial to hippocampus projection ( Fujita et al, 2020 ), and the SuM may instead route its influence on the hippocampus via e.g., the septum ( Pan and McNaughton, 2004 ; Griguoli and Pimpinella, 2022 ).…”
Section: The Social Hippobellum?mentioning
confidence: 99%
“…MS is considered to be a key brain region regulating sleep-wake state and hippocampus-dependent memory, and has become a research hotspot in the field of sleep cognition in recent years. MS contains highly interconnected neurons: cholinergic, gamma-aminobutyric acid (GABA), and glutamatergic neuronal populations synchronously coordinate sleep-wake and cognitive processes (Griguoli and Pimpinella, 2022). The hippocampal CA1 region is considered to be the core region of hippocampusdependent learning and memory processing, and it mainly forms interconnections with the cerebral cortex (Uebele et al, 2009), which is the key region to determine spatial learning and memory (Yousefi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroanatomical analysis revealed that autistic patients show smaller neurons and increased cell density in the BF as compared to age-matched healthy individuals ( 94 ). Moreover, diminished activity of cholinergic neurons in the basal forebrain was reported in mice ( 95 ).…”
Section: Genetic and Neural Mechanisms Of Abnormal Sleep–wake Rhythm ...mentioning
confidence: 99%